The Role of Treasury bills to the most important monetary variables in Iraq for the period 1990 – 2013 - العاني عماد محمد علي; جوحي نسرين حسن (Journal of Economics and Administrative Sciences, 2017)
The treasury bills one internal government debt instruments in iraq that were used to finance temporary deficits in the government budget, There fore the government resorted to issuing for the purpose of providing liquidity, As well as to invest in productive progects, After that it was financing the budget deficit by the monetary authovity of the central baalpennek [the new cash velease] which led to negative effects on the Iraqi econome, Thus we find that the treasury transfers have formed alarge proportion of the gross domestic government debt to finance the deficit ayear ago 2003. Based on the instruction sell securities in auction, Government issued treasury transfers through the establishment of auctions in the central bank of Iraq with the duration of 91,182,365 days during the period 2013\2014, As the central bank takes on the purchase and sale of commercial banks and financial institutions, And it is expected that he could exploit the increased is suance of treasury transfers as anon in flationary sources to the extent that it may affect the monetary policy variables in order to control the size of the money supply and the interest rate and the fight against in flation and the stability of the local currency value. Find it finds that the continused occurrence of the deficit in the government budget was not an accumulation of government debt from issuing treasury transfers but the main reason is due to the increase in government spending, Any sense that the treasury transfers can act like treasury transfers to control the excess liquidity and restrict in flationary constrains through higher interest rates which is working to with draw part of the excess reserves at commercial bangs financial institutions and baaltala reduce their ability to grant credit, Therefore they could exercise such appositive role in influencing the monetary policy[central bank] make them the strength to prevail to support the effectiveness of monetary policy